Eurotium cristatum, a potential probiotic fungus from Fuzhuan brick tea, alleviated obesity in mice by modulating gut microbiota. Issue 8 (30th July 2019) - Kang, Dingding; Su, Meng; Duan, Yanwen; Huang, Yong
Abstract : Eurotium cristatum from Fuzhuan brick tea may be utilized as a potential probiotic fungus against high-fat diet-induced obesity by modulating gut microbiota. Abstract : Obesity is one of the major public health problems worldwide, mainly resulting from unhealthy lifestyles and diet. Gut microbiota dysbiosis may lead to obese humans and animals. Modulating gut bacteria through probiotics or certain dietary supplements could normalize gut microbiota and subsequently alleviate obesity. The daily consumption of Fuzhuan brick tea (FBT) or its extracts has been observed to alleviate obesity in humans and experimental animals. In this study, high-fat diet (HFD)-induced obesity in mice, such as body weight gain and fat accumulation, was prevented by the consumption of Eurotium cristatum, the dominant fungus during the manufacturing and storage of FBT. The dysbiosis of gut microbiota in C57BL/6J mice was also partially normalized. E. cristatum was able to modulate both gut fungal and bacterial compositions, based on the analysis of the microbiota composition of mice fecal samples ( n = 5). E. cristatum increased acetate and butyrate-producing bacteria in mouse gut. There was five times more butyrate in the fecal samples from mice fed with E. cristatum than that from untreated HFD mice. Our results suggest that E. cristatum may be used as a probiotic fungus to alleviate obesity and to modulate gut microbiota in humans beneficially.